Effects of an isatin derivative on tumor cell migration and angiogenesis. Issue 2 (8th January 2020) - Chang, Yunsong; Yuan, Yuan; Zhang, Qian; Rong, Yao; Yang, Yang; Chi, Ming; Liu, Zhen; Zhang, Yongmin; Yu, Peng; Teng, Yuou
Abstract : Compound 5-61, a 5-(2-carboxyethenyl)isatin derivative was previously shown to have potent anticancer activity. Its effect on angiogenesis was further explored in this study. Abstract : Compound 5-61, a 5-(2-carboxyethenyl)isatin derivative was previously shown to have potent anticancer activity. Its effect on angiogenesis was further explored in this study. Notably, 5-61 showed selective cytotoxicity against liver hepatocellular carcinoma HepG-2 cells (IC50 = 7.13 nM). 5-61 powerfully induced apoptosis and G2 /M phase arrest as well as inhibited the migration of HepG2 cells. Additionally, 5-61 clearly diminished tube formation and the actin arrangement in HUVECs. The physiological anti-angiogenic effects of 5-61 were further assessed by chick chorioallantoic membrane assays in vivo . The effects exerted by 5-61 were found to be mediated by VEGF along with its downstream signaling pathways including the PI3K/Akt/mTOR pathway and mitogen-activate protein kinase pathways (ERK). These results suggested that 5-61 is a potential tumor angiogenesis inhibitor that functions by interrupting the auto-phosphorylation of AKT, mTOR, and ERK 1/2.